Optimalisasi Konfigurasi Fasa Vertikal Pada Saluran Udara Tegangan Ekstra Tinggi - Ruwah Joto; Dhesah Kharisma, Dhimas; Mochammad Mieftah; Aly Imron (Elposys: Jurnal Sistem Kelistrikan, 2025)
The dangers arising from the 500 kV extra high voltage overhead lines to the surrounding environment can actually be minimized in several ways. One of the methods is to change the configuration of the conductor arrangement. Based on the laws in field theory which state that the magnitude of the field quantity on a charged conductor can differ depending on the distance, area, or volume, an analysis was carried out to understand the effect of the phase arrangement on the electric field intensity under the 500 kV overhead transmission line. The Finite Difference Method uses a numerical approximation to the partial derivative of the differential equation describing the electric field. The use of the Hybrid Tower combines vertical and horizontal designs to achieve a balance between low electric fields and land efficiency. Of the 36 combinations of phase arrangements on transmission lines with a double-circuit vertical configuration, there is a large variation in the resulting field intensity. Information on the phase arrangement that produces the smallest field intensity is very important. The arrangement of 36 (arrangement T1-S1-R1: T2-S2-R2) produces the lowest electric field intensity. Compared with the super bundle arrangement (arrangement R1-S1-T1: R2-S2-T2), there is a decrease in field intensity of up to 45.842%, while compared with the low reactance arrangement (arrangement R1-S1-T1: T2-S2-R2), there is a decrease in field intensity of up to 33.374%.